A clinical study on diagnostic, clinicopathological correlation of acute cholecystitis - Mohandhas, Gopalakrishnan; Nallathambi, Vijayan; Iyenkar, Srinivasan Ravi (International Surgery Journal, 2018)
Background: Acute cholecystitis (AC) one of the common surgical emergency. Thorough understanding of the profile of clinical presentation may help in clinical decision making in resource poor settings. Hence the present study is conducted with the objectives to study the clinico pathological profile of acute cholecystitis cases presenting to a tertiary care teaching hospital and to describe the management and complications. Methods: A prospective observational study was conducted in the department of emergency and general surgery of Dhanalakshmi Srinivas medical college and hospital. The study included 50 clinically confirmed cases of acute cholestasis presented between June 2017 to December 2017. Results: A total of 50 subjects were included in the final analysis. The highest proportion of subjects were in 46 to 50 years (28%) or 51 and above (26%) age groups. Females (56%) outnumbered males (44%). Right hypo chondral tenderness (100%) was the most common clinical presentation. The proportion of calculous and acalculous cholecystitis was 84% and 14% respectively, remaining 2% of cases were malignancies. The proportion of emergency and elective surgeries were 12% and 88% respectively. The most common organism cultured was E. coli in 24%, Staph, aureus in 14%, salmonella in 2% of the population. Post-operative wound infection was more commonly seen in culture positive cases. Conclusions: Health care practitioners at various levels need to have a good understanding of varied clinical presentation of acute cholecystitis and different management options, their advantages, and disadvantages to be able to treat the condition effectively.